SIKAP DAN KEPUASAN KONSUMEN TERHADAP PAKET MENU LELE TERBANG, KAITANNYA DENGAN BAURAN PEMASARAN DI RUMAH MAKAN SAMBAL LALAP BANDAR LAMPUNG - Sulfiana, Wayan Nila; Murniati, Ktut; Indriani, Yaktiworo (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This study aims to determine the consumers’ characteristics of attitude and satisfaction; in adition to its correlation with marketing mix of lele terbang package in Sambal Lalap Restaurant Bandar Lampung. Research location was determined purposively. The number of interviewed sample was 59 respondents that were chosen by convennion sampling. The first and fourth objectives were solved by descriptive analysis. The first and fourth purposes were analyzed descriptively, the second purpose was analyzed by using Fishbein’s multiattribute, and the third purpose was analyzed by using Customer Satisfaction Index (CSI) and Importance performance Analysis (IPA). The result showed that consumers were dominated by 19 to 24 years old women, and was bachelor students who had income last than < Rp1,500,000.00 per month and frequency of purchase the package was 1 to 3 times per week. The score of consummer attitude had been positive, some attributes with the highest score were taste, price, halal, cleanness, and the comfortable of the place. In overall, the score of CSI was feeling satisfied in consuming the menu packages of lele terbang. Based on the analysis of IPA, the attribute at the Kuadran I (main priority) was hygiene attribute. Moreover, the attribute in Kuadran II (hold the prestation) were taste, price, halal, cleanness, and the comfortable of the place. Attribute in Kuadran II (low priority) were aroma, size, benefit, location, and facility. While, attribute in Kuadran IV (excessive) were the attribute of menu and parking area. The marketing of menu package lele terbang at Sambal Lalap Restaurant had implemented marketing strategy (marketing mix). Key words: Attitude, CSI, IPA, marketing, package menu of lele terbang